Drug−disease interaction: Crohn's disease elevates verapamil plasma concentrations but reduces response to the drug proportional to disease activity - Sanaee, Forough; Clements, John D.; Waugh, Alistair W. G.; Fedorak, Richard N.; Lewanczuk, Richard; Jamali, Fakhreddin (British journal of clinical pharmacology, 2011)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Inflammatory conditions such as Crohn's disease are associated with cardiovascular complications. Inflammation also substantially reduces clearance of some cardiovascular drugs. It has also been shown that in rheumatoid arthritis, an elevation in verapamil concentration does not result in increased response. WHAT THIS STUDY ADDS • A reduced response upon increased verapamil concentration in another inflammatory condition, inflammatory bowel disease, with different aetiology from arthritis was found. Interestingly, however, a mere affliction with the disease is not sufficient to alter pharmacokinetics and pharmacodynamics since we found that the alteration is a function of disease severity. There is a remarkable reverse correlation between the disease severity and response to verapamil. Our observation suggests a complex relationship between pharmacokinetics and pharmacodynamics which may have implications beyond the disease and the drug studied herein. AIM Inflammation is involved in the pathogenesis of cardiovascular diseases that includes reduced response to pharmacotherapy due to altered pharmacokinetics and pharmacodynamics. It is not known if these effects exist in general in all inflammatory conditions. It also remains unknown whether in a given population the effect is a function of disease severity. We investigated whether pharmacokinetics and pharmacodynamics of a typical calcium channel inhibitor are influenced by Crohn's disease (CD), a disease for which the disease severity can be readily ranked. METHODS We administered 80 mg verapamil orally to (i) healthy control subjects (n= 9), (ii) patients with clinically quiescent CD (n= 22) and (iii) patients with clinically active CD (n= 14). Serial analysis of verapamil enantiomers (total and plasma unbound), blood pressure and electrocardiograms were recorded over 8 h post dose. The severity of CD was measured using the Harvey‐Bradshaw Index. RESULTS CD substantially and significantly increased plasma verapamil concentration and in a stereoselective fashion (S, 9‐fold; R, 2‐fold). The elevated verapamil concentration, however, failed to result in an increased verapamil pharmacodynamic effect so that the patients with elevated verapamil concentration demonstrated no significant increase in response measured as PR interval and blood pressure. Instead, the greater the disease severity, the lower was the drug potency to prolong PR interval (r= 0.86, P < 0.0006), CONCLUSIONS CD patients with severe disease may not respond to cardiovascular therapy with calcium channel blockers. Reducing the severity increases response despite reduced drug concentration. This observation may have therapeutic implication beyond the disease and the drug studies herein.